Analysis of armature inter‐turn fault in the multiphase synchronous generator‐rectifier system. Issue 7 (7th June 2019) - Sun, Yuguang; Wang, Shanming; Du, Wei; Mu, Shujun
Abstract : The multiphase synchronous generator‐rectifier system could provide an ideal DC power source for more electric aircraft (MEA). When the inter‐turn short‐circuit fault occurs in phase windings of the generator, a large short‐circuit current would be introduced inside the armature windings, which could cause severe damages to the system for overheat in the windings and irons as well as huge electromagnetic forces on the end coils. To improve the reliability of the MEA, this study researches on the inter‐turn fault of the multiphase generator‐rectifier system including the theoretical analysis, numerical simulation and experiment verification. A 12‐phase system is taken, for example, and a multi‐loop mathematical model is built up to calculate all voltages and currents in the multiphase synchronous generator‐rectifier system with armature inter‐turn fault. Many factors are thoroughly considered in the model including the location and short turns of fault, space harmonics of the air‐gap magnetic field and the changing circuit topology of the system. Moreover, the mathematical model is verified by fault experiment results. Moreover, the electric characteristics of the fault are summarised, which could provide a quantitative basis for early detection of the inter‐turn faults in the multiphase generator‐rectifier system.